North Korean cinema : a history - Schönherr, Johannes (McFarland, 2012)
This volume chronicles the history of North Korean cinema from its beginnings to today, examining the obstacles the film industry faced as well as the many social problems the films themselves reveal. It provides detailed analyses of major and minor films and explores important developments in the industry within the context of the concurrent social and political atmosphere.